2016
DOI: 10.1093/eurpub/ckw207
|View full text |Cite
|
Sign up to set email alerts
|

Global region of birth is an independent risk factor for type 2 diabetes in Stockholm, Sweden

Abstract: In Stockholm, type 2 diabetes (T2D) is a public health concern and much more prevalent in areas with a high proportion of foreign-born individuals. One in five individuals in Stockholm County are born outside of Sweden, and we therefore investigated if global region of birth was associated with diabetes risk, adjusting for established risk factors. Cross-sectional data from the population-based Stockholm Public Health Survey 2010 ( N = 69 115) was combined with registry-based information on country of birth gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Education was recoded as ‘basic education’ corresponding to 9 years or fewer, ‘secondary education’ corresponding to 10–12 years of schooling and ‘college or university education’ – named as ‘higher education’. Alcohol consumption was categorised into ‘no’, ‘low’, ‘medium’ and ‘high’ with different cut-off points for men and women, and those were ‘0’, ‘>0 to ≤24 g/d’, ‘>24 to ≤60 g/d’ and ‘>60 g/d’ for men; and ‘0’, ‘0 to ≤15⋅4 g/d’, ‘>15⋅4 to ≤50 g/d’ and ‘> 50 g/d’ for women, respectively (5) . Smoking status was created with the variables ever smoked (‘Have you ever smoked as good as daily, for at least 6 months?’ Answer with ‘yes’ or ‘no’) and current smoking (‘Are you currently smoking daily?’ Answer with ‘yes’ or ‘no’) and categorised into ‘never smoked’, ‘current smoker’ and ‘former smoker’ (5) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Education was recoded as ‘basic education’ corresponding to 9 years or fewer, ‘secondary education’ corresponding to 10–12 years of schooling and ‘college or university education’ – named as ‘higher education’. Alcohol consumption was categorised into ‘no’, ‘low’, ‘medium’ and ‘high’ with different cut-off points for men and women, and those were ‘0’, ‘>0 to ≤24 g/d’, ‘>24 to ≤60 g/d’ and ‘>60 g/d’ for men; and ‘0’, ‘0 to ≤15⋅4 g/d’, ‘>15⋅4 to ≤50 g/d’ and ‘> 50 g/d’ for women, respectively (5) . Smoking status was created with the variables ever smoked (‘Have you ever smoked as good as daily, for at least 6 months?’ Answer with ‘yes’ or ‘no’) and current smoking (‘Are you currently smoking daily?’ Answer with ‘yes’ or ‘no’) and categorised into ‘never smoked’, ‘current smoker’ and ‘former smoker’ (5) .…”
Section: Methodsmentioning
confidence: 99%
“…Answer with 'yes' or 'no') and current smoking ('Are you currently smoking daily?' Answer with 'yes' or 'no') and categorised into 'never smoked', 'current smoker' and 'former smoker' (5) . Physical activity during the last 12 months was assessed through a combination of the following variables: walking/cycling, exercise, daily activities and/or work, domestic tasks, and sedentary activities.…”
Section: Assessment Of Other Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to adults, higher rates of obesity and low physical activity are found in groups with low socio-economic position (SEP), and it has been speculated that these factors are the main causes behind the higher prevalence and earlier onset of type-2 diabetes (T2D) among adults with low SEP [ 15 ]. Furthermore, studies have shown that immigrants to Sweden have a significantly higher risk of T2D than Swedish-born individuals even when adjusted for established risk factors [ 16 ]. Today it is recognised that development of both obesity and T2D is driven by interacting genetic and environmental factors and is preventable to a large extent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%